Cryogels from albumin and low methoxyl amidated pectin as a matrix for betalain encapsulation. Issue 11 (12th August 2020) - Chaux‐Gutiérrez, Ana M; Pérez‐Monterroza, Ezequiel J; Granda‐Restrepo, Diana M; Mauro, Maria A
Abstract: Betalain from beetroot ( Beta vulgaris ) was encapsulated in cryogels consisting of albumin (ALB) and albumin‐pectin (ALB‐PEC). The color characteristics, encapsulation efficiency (EE), and release profile, as well as the molecular interactions and morphological characteristics of the cryogels, were evaluated. All of the cryogels had a reddish‐purple tonality and showed high EE, with values between 88% and 97%. The release profile was affected by the PEC concentration and the methodology used in the preparation of the cryogels (pre‐load or post‐load). The betalain release percentage after 4 hr of exposure, ranged between 10%–12% (pH 2), 29%–33% (pH 7), and 26%–31% (pH 10) for pre‐loaded cryogels, whereas for post‐loaded cryogels, the ranges were 8%–18% (pH 2), 21%–43% (pH 7), and 30%–49% (pH 10).The ALB cryogels showed a compact structure, whereas the ALB‐PEC cryogels showed a cohesive and fibrous structures compared with that of the ALB cryogels. Practical application: Cryogels from albumin and low methoxyl amidated pectin can be considered an interesting tool for encapsulation of bioactive compounds such as betalain and formulate functional food. Cryogels are a potential biodegradable matrix as an alternative for a controlled release system of the bioactive compounds.